How to Manage an Effective Laboratory for Science Learning in Schools? - Nyoto Suseno; Riswanto Riswanto; M. Barkah Salim; Dedy Hidayatullah; I Gede Rasagama (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
The role of school laboratories is vital in helping junior high school students learn science. Many schools have laboratory facilities but are underutilized. This study aims to optimize the role of school laboratories through action research. In three cycles, the writer carried out the SMP Negeri 2 Metro research and SMP Negeri 6 Metro. The first cycle carried out technical guidance to the laboratory manager. Still, the results were not as expected due to communication problems to understand the principal's importance of incomplete laboratory improvement. The second cycle is carried out by mentoring the laboratory management. This includes the making of the laboratory management, inventory, and labeling, and creating work programs. This cycle two treatment also has not shown the results as expected. The reflection results found that the root of the problem was that the teachers and the laboratory manager believed that practicum activities needed time. So, it had to be carried out outside of class hours to require additional time, effort, and cost. To overcome this problem, in the third cycle, a workshop on making a practicum guide and Standard Operating Procedure (SOP) of practicum was developed according to the lesson schedule, then a trial was conducted. Data collection uses documentary, interview, and Focus Group Discussion (FGD) methods to explore the root of the problem and the solution. Data processing uses a qualitative approach with steps: data collection, selection, and grouping, tabulation, description, interpretation, and conclusions. Based on the results of action research data analysis, it can be concluded: First, management improvement and inventory of laboratory tools and materials as well as making practical SOPs, which are effective in optimizing the role of science laboratories in supporting the learning process; Second, the use of SOP practicum according to the lesson schedule is quite efficient in saving time, effort, and costs. According to the results of this study, it is recommended that for the laboratory to be optimal in supporting learning, laboratory management must be orderly equipped with SOPs, and inventory of tools and materials must be good.